Pengaruh umur pejantan sapi Simmental terhadap tingkah laku reproduksi, kualitas semen segar dan jumlah produksi semen beku - Widya Yanuarista; Enny Tantini Setiatin; Daud Samsudewa (Universitas Sebelas Maret, 2022)
Objective: The objective of this research was to determine the appearance of reproduction behavior, fresh semen quality and amount of frozen semen production based on different age of Simmental bulls.Methods: The material was used 15 Simmental Bulls with average of body weight 822,2 ± 86,53 kg and CV 10,53%. Material divided into 3 groups; age <4 years (T1), age 4-6 years (T2) and age >6 years (T3). The appearance of reproduction behavior (duration, interval, frequency), duration semen collection, fresh semen quality and frozen semen production. Kruskall Wallis test was used in study and followed by mann Withney U-test when data is a significant.Results: The result showed that the non-parametric statistical results of the Mann Whitney U-Test was significantly different (P<0,05) specifically duration of kissing T1 (0 second); T2 (0 second); T3 (2,90 second), interval of mounting T1 (43,19 ± 8,98 second); T2 (51,31 ± 11,07 second); T3 (87,42 ± 13,74 second), duration semen collection T1 (197,21 ± 11,68 second); T2 (207,35 ± 42,33 second); T3 (361,51 ± 39,94 second), and mass motility T1 (2,6 ± 0,20); T2 (2,84 ± 0,15); T3 (2,28 ± 0,35) in Simmental bulls of different age. Conclusions: Decreasing libido and the quality from the Bulls occured at >6 years old. The productive age of excellent bulls is at the age of 4-6 years by displaying the best libido display and optimal sperm quality and frozen semen production.